IKEA: self watering plant pot / Siti Nuratiqah Asman - Asman, Siti Nuratiqah (2022)
IKEA is a well-known company for manufacturing wide range of furniture which has innovative designs and affordable. The main focus in this company analysis is to investigate, identify and analyze the problems faced by PS Fejö self-watering plant that is produced by IKEA so that solutions can be created to solve the problems. The first problem of the product is it may become a place for mosquito to breed. The design of the pot has a poor drainage system and open reservoir which makes the pot an ideal place for breeding mosquitos. The second problem is potential concentration of toxic mineral salts due to continuous flow of water which will lead to poor root growth. There are few solutions to overcome the problem. The first one is the plant pot is attached with an enclosed-container which is specialized to store water resources. This is to protect the water from exposed to air and mosquitos. Next is by adding electronic sensor to the pot which will detect and measure the water content in the soil.